2002
DOI: 10.1046/j.0022-3042.2001.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone decreases retinal endothelial cell water and solute flux coincident with increased content and decreased phosphorylation of occludin

Abstract: Corticosteroids provide an effective treatment to reduce edema for conditions in which the blood-brain or blood-retinal barrier is compromised. However, little is known about the mechanism by which these hormones affect endothelial cell function. We hypothesized that hydrocortisone would reduce transport of water and solutes across bovine retinal endothelial cell (BREC) monolayers coincident with changes to the tight junction protein occludin. Treatment of BREC with 103 nM hydrocortisone for two days significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(131 citation statements)
references
References 60 publications
6
120
0
5
Order By: Relevance
“…15 We obtained CSF from healthy, iron-sufficient, and anemic iron-deficient infant monkeys. The results from this experiment are shown in Figure 3A and clearly show increased iron release from ECs upon exposure to CSF from iron-deficient monkeys versus CSF from iron sufficient monkeys.…”
Section: Resultsmentioning
confidence: 99%
“…15 We obtained CSF from healthy, iron-sufficient, and anemic iron-deficient infant monkeys. The results from this experiment are shown in Figure 3A and clearly show increased iron release from ECs upon exposure to CSF from iron-deficient monkeys versus CSF from iron sufficient monkeys.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms of intravitreal corticosteroids include reduction of retinal capillary permeability by increasing the activity and/or density of tight junctions in the retinal capillary endothelium, 64 inhibition of the VEGF gene expression, inhibition of the VEGF metabolic pathway, 65 and suppression of intracellular adhesion molecule-1 (ICAM-1)-mediated leucocyte adhesion to vessel walls. 66 Corticosteroids help keep vision stable, but increase the incidence of cataracts and glaucoma.…”
Section: Anti-inflammatory and Immunosuppressive Agentsmentioning
confidence: 99%
“…Glucocorticoids also develop the properties of the Blood-Retinal Barrier (BRB) [114]. It has been observed that occludin phosphorylation was reduced after 4 hours following the initiation of glucocorticoid treatment, and occludin expression was increased simultaneously in the bovine retinal endothelial cell layer [114].…”
Section: Effects Of Dexamethasone On Tight Junction Proteinsmentioning
confidence: 96%
“…Occludin increases in the in vitro vascular endothelial barrier models, and it was observed that occludin mRNA increased. It was also shown that it was hydrocortisone that caused occludin dephosphorylation [114].…”
Section: Effects Of Dexamethasone On Tight Junction Proteinsmentioning
confidence: 99%
See 1 more Smart Citation